2013
DOI: 10.1530/endoabs.32.p74
|View full text |Cite
|
Sign up to set email alerts
|

Bone quality, as measured by trabecular bone score (TBS), in patients with primary hyperparathyroidism

Abstract: Spinal Deformity Index <0.0001 40 (43.5) 8 (8.2) No. of patients with VFx <0.0001-2.39±1.79

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…The finding that the effect of denosumab in terms of ΔALP is more evident in individuals with PHPT than in those with PO suggests that denosumab‐related reduction of bone turnover may be greater in individuals with PHPT than in those with PO. In individuals with PHPT, the greater bone turnover and consequent bone damage are thought to be mainly due to the excessive activation of RANK/RANKL pathway . On the basis of these considerations, the present finding of a dramatic positive effect of denosumab on BMD in individuals with PHPT could be considered somewhat expected.…”
Section: Discussionmentioning
confidence: 54%
See 3 more Smart Citations
“…The finding that the effect of denosumab in terms of ΔALP is more evident in individuals with PHPT than in those with PO suggests that denosumab‐related reduction of bone turnover may be greater in individuals with PHPT than in those with PO. In individuals with PHPT, the greater bone turnover and consequent bone damage are thought to be mainly due to the excessive activation of RANK/RANKL pathway . On the basis of these considerations, the present finding of a dramatic positive effect of denosumab on BMD in individuals with PHPT could be considered somewhat expected.…”
Section: Discussionmentioning
confidence: 54%
“…Although use of denosumab has been suggested as an interesting approach to the treatment of PHPT because it inhibits the RANK/RANKL pathway, which is important in the catabolic actions of PTH, no data were available in individuals with PHPT. The results of the present study are therefore important because they suggest for the first time that denosumab may be effectively used in older women with PHPT.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A large number of studies have con rmed that the lumbar TBS can be used to evaluate not only lumbar vertebra bone quality but also femoral neck and hip bone quality and is a powerful tool for evaluating bone quality and predicting fracture risk. In particular, for elderly patients with lumbar osteoarthritis, people with brittle fractures due to a BMD T value > -2.5, patients with type 2 diabetes, and patients with glucocorticoid-induced osteoporosis, the TBS is superior to the BMD for predicting fracture risk [3][4][5][6]29] . Several cross-sectional and prospective studies have shown associations between the lumbar TBS and lumbar fractures, hip fractures, and other types of fractures in postmenopausal women [30] .…”
Section: Changes In the Tbs Before And After Bariatric Surgerymentioning
confidence: 99%